2017
DOI: 10.15561/20755279.2017.0401
|View full text |Cite
|
Sign up to set email alerts
|

The effects of three different type of exercises on aerobic and anaerobic power

Abstract: Purpose:The study was conducted with the aim of investigating the effects of three different types of exercise: bicycling, plyometric and weight on aerobic and anaerobic power. Material:Sample size 30 students recreational athletes aged 23,19 years. The athletes were divided into 3 groups of 10 subjects (bicycle, plyometric, weight). The program for 6 weeks included: 3 different exercises planned for 30 minute/3 days/week. Body weight, vertical jump and 20-meter shuttle running tests were measured for each gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…Leisure activities provide students with positive social behaviors and a quality lifestyle, as well as protecting the young population from harmful habits [13][14][15]. The process of training of the young generation to target proactive behaviors and attitudes is one of the primary goals of promoting leisure activities based on diversification of motivation, improvement of physical fitness and enhancement of motor skills [16][17][18]. Despite these positive contributions to recreational activities, it is observed that individuals do not participate in such activities, for reasons that are very important for them, or they cannot attend due to various obstacles [19].…”
Section: Introductionmentioning
confidence: 99%
“…Leisure activities provide students with positive social behaviors and a quality lifestyle, as well as protecting the young population from harmful habits [13][14][15]. The process of training of the young generation to target proactive behaviors and attitudes is one of the primary goals of promoting leisure activities based on diversification of motivation, improvement of physical fitness and enhancement of motor skills [16][17][18]. Despite these positive contributions to recreational activities, it is observed that individuals do not participate in such activities, for reasons that are very important for them, or they cannot attend due to various obstacles [19].…”
Section: Introductionmentioning
confidence: 99%
“…Other research has analyzed the relationship between HRQoL and PA [15][16][17][18][19][20][21]. Research on the relationship between HRQoL and PA, to date, has rarely investigated how this relationship differs across objective and subjective measures of PA.…”
Section: Introductionmentioning
confidence: 99%
“…In this sense, the World Health Organization (WHO) published the European Physical Activity Strategy for WHO European Region 2016–2025, which proposes to ensure the adaptability of physical education programs in different contexts [8]. The need to change and adapt the content of the Physical Education discipline is essential in order to increase attractiveness in the context of a society that is increasingly inactive and reluctant to practice physical exercise [9,10,11,12,13]. Qualitative changes in physical education and sport occur when educators and teachers experienced directly and understood the implications of certain techniques and practices.…”
Section: Introductionmentioning
confidence: 99%